Flowering and fruiting of the dioecious canopy tree Cercidiphyllum japonicum over an 8-year period in central Japan. Issue 1 (2nd January 2022) - Sakio, Hitoshi; Kubo, Masako
ABSTRACT: To investigate the reproductive traits of the dioecious canopy tree Cercidiphyllum japonicum, we performed visual surveys from 2000 to 2007 to assess the flowering and fruiting of 59 individuals in a riparian forest in central Japan. Flowering and fruiting were assigned to ranked categories, where 1 indicated none and 5 indicated abundant production throughout the canopy. In addition, we used conical seed traps to assess the seed production of this species at the center of the forest. Of the 59 study individuals, 20 female and 26 male trees were >26 cm in diameter at breast height (DBH) and classified into the canopy layer. The remaining smaller individuals were non-reproductive and, excluding one, were classified into the sub-canopy layer. We estimated that C. japonicum may require 100 years of growth to reach 26 cm in DBH in a riparian forest. Both sexes produced abundant flowers in all years, and males exhibited slightly higher flowering and lower variation than females. Individuals with a DBH > 50 cm tended to flower very abundantly, and this pattern was consistent with trees over 1 m in DBH. Seed-trap surveys indicated that C. japonicum seeds were dispersed annually, with inter-annual variation. We conclude that C. japonicum is quite slow to reach sexual maturity, but can produce very abundant flowers, fruits, and seeds annually throughout its long lifespan.